Analisis Penyusunan Laporan Keuangan Berdasarkan Sak Emkm Pada Usaha Percetakan Cv. Sk Print Di It Center Manado - Paendong, Yelly Sjenny; Lendeng, Olivia Vannesa (Cattleya Darmaya Fortuna, 2024)
Lendeng, Olivia. 2024. Analysis of the Preparation of Financial Statements Based on SAK EMKM at CV Printing Business. SK Print at It Centre Manado. Thesis. Department of Accounting. Politeknik Negeri Manado. Supervisor I Opa Mustopa, SE, MSi. CAAT and Supervisor II: Belthasar Trito Siahaan, M.Si. This research was conducted at one of the MSMEs, namely the printing business CV. SK Print at IT Center Manado. The main objective of this research is to analyze and provide recommendations to MSMEs regarding the preparation of financial reports in accordance with accounting standards, namely SAK EMKM. In this accounting standard there are three financial statements in it, namely the income statement, statement of financial position (balance sheet) and notes to financial statements (CALK). This research is qualitative research that uses a case study approach. Data collected through interviews. The results of this study indicate that the financial statements of CV SK Print are not in accordance with SAK EMKM. This MSME also still prepares simple financial reports that are made directly by the owner. The owner also has obstacles faced, namely a lack of understanding of accounting so that he cannot compile financial reports in accordance with accounting standards. The CV. SK Print company should do bookkeeping so that it can make financial reports, and should prepare financial reports according to SAK EMKM.